Effect of hot extrusion temperature on graphene nanoplatelets reinforced Al6061 composite fabricated by pressure infiltration method. (June 2020) - Shao, Puzhen; Chen, Guoqin; Ju, Boyu; Yang, Wenshu; Zhang, Qiang; Wang, Zhijun; Tan, Xin; Pei, Yinyin; Zhong, Sujuan; Hussain, Murid; Wu, Gaohui
Abstract: In the present work, 0.6 wt% graphene nanoplatelets reinforced 6061Al (GNPs/6061Al) composite was prepared by pressure infiltration process and hot extruded (HE) at 420 °C∼500 °C in order to investigate the evolution of GNPs in different extrusion temperature, which has not been reported yet. The GNPs agglomeration were eliminated by extrusion and were arranged in an orientation. In the sample extruded at 420 °C, the dispersion effect was not significant and agglomeration of large-sized GNPs was still found. However, the agglomeration of the GNPs was eliminated when extruded at 450 °C, and waved structure, exfoliation and bend of GNPs were observed. While in the sample at 500 °C, interlayer sliding of GNPs and interfacial reaction product Al4 C3, due to excessively high extrusion temperature, were detected. The composites extruded at 450 °C showed the highest yield strength and ultimate tensile strength of 389 MPa and 500 MPa, respectively, which increased 16.8% and 40.1% comparing with the unreinforced matrix. The present results indicate that the uniform dispersion of graphene is still one of the main challenges in Graphene/Al composites, while the deformation treatment provides the possibility of further dispersion of graphene. Graphical abstract: Image 10409751